The Quality of "Aurevya" Ready-to-Wear Clothing as Sustainable Fashion Through Wastra and Denim Upcycling - Zulfani, Mila; Wahyuningsih, Sri Endah (Journal of Creativity Student, 2026)
This study is motivated by the growing need for fashion innovation that emphasises not only aesthetic value but also sustainability principles and the preservation of Indonesian traditional textiles (wastra). The purpose of this research is to develop and evaluate the quality of the ready-to-wear fashion product "Aurevya," made from tenun bulu fabric and upcycled denim, as an implementation of the concept Wastra Reimagined: Tradition in Motion. A quantitative descriptive method was employed, with data collected through a structured product quality assessment. The evaluation involved 25 panellists, comprising five fashion experts and 20 trained panellists from the Fashion Education program. The assessed aspects included design, aesthetics, sewing techniques and finishing, garment performance, and uniqueness. The results indicate that the Aurevya garment achieved an average feasibility score of 97%, indicating it is highly feasible. The uniqueness aspect obtained the highest score at 98%, demonstrating the successful integration of traditional textiles and upcycled materials within a contemporary design approach. These findings suggest that applying sustainable fashion principles through upcycling techniques and waste exploration can produce high-quality, functional, ready-to-wear garments with a strong design identity.